1998
DOI: 10.1006/bare.1997.0070
|View full text |Cite
|
Sign up to set email alerts
|

Audit Market Competition: Auditor Changes and the Impact of Tendering

Abstract: Increased competition within the external audit market and the recent phenomenon of audit tendering has renewed interest in the factors influencing auditor changes. In this paper, a questionnaire instrument is used to elicit perceptions of the factors which influence auditor-client realignments in this new environment and to indicate the relative influence of economic and behavioural factors. Positive, statistically significant associations were found between unsolicited approaches and the consideration of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 36 publications
1
56
1
1
Order By: Relevance
“…Several writers (Bedingfield & Loeb, 1974;Eichenseher & Shields, 1983;Lynn, 1988;Beattie & Fearnley, 1998) have concluded that audit fees are an important factor in a company's decision to change auditors and then in a company's consideration of its new auditor. It appears that accounting firms are aware of the importance of audit prices, and studies (DeAngelo, 1981a;Simon & Francis, 1988;Ettredge & Greenberg, 1990) show that firms sometimes 'lowball' their fees in order to obtain an audit.…”
Section: Discussionmentioning
confidence: 97%
“…Several writers (Bedingfield & Loeb, 1974;Eichenseher & Shields, 1983;Lynn, 1988;Beattie & Fearnley, 1998) have concluded that audit fees are an important factor in a company's decision to change auditors and then in a company's consideration of its new auditor. It appears that accounting firms are aware of the importance of audit prices, and studies (DeAngelo, 1981a;Simon & Francis, 1988;Ettredge & Greenberg, 1990) show that firms sometimes 'lowball' their fees in order to obtain an audit.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of listed companies the securities market generally has a preference or attaches some form of premium to a company being audited by a Big 5 audit firm (Beattie & Fearnley, 1998). In the case of unlisted companies the Big 5 audit firms can rely less on their reputation to impress their clients but instead have to demonstrate in a more observable way that the audit they perform is superior to that of a non-Big 5 audit firm.…”
Section: Research Aimsmentioning
confidence: 99%
“…Nevertheless, there are argumentsin the inadequacyof explaining the reasons and rationale for the remarkable statistics of auditor switching. This is because they neglect the behavioural factors and present only partial explanation regarding auditor switching (Beattie &Fearnley 1998). Moreover, corporate governance mechanisms influence company's auditor switching determination (Lin & Liu 2010).…”
Section: Literature Reviewmentioning
confidence: 99%